2009
DOI: 10.1111/j.1750-2659.2008.00058.x
|View full text |Cite
|
Sign up to set email alerts
|

Avian influenza surveillance in wild birds in the European Union in 2006

Abstract: Background  Infections of wild birds with highly pathogenic avian influenza (AI) subtype H5N1 virus were reported for the first time in the European Union in 2006. Objectives  To capture epidemiological information on H5N1 HPAI in wild bird populations through large‐scale surveillance and extensive data collection. Methods  Records were analysed at bird level to explore the epidemiology of AI with regard to species of wild birds involved, timing and location of infections as well as the applicability of differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
69
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(75 citation statements)
references
References 16 publications
4
69
1
1
Order By: Relevance
“…This observation is consistent with historic surveillance results of higher isolation rates from mallards, and supports the important role that this species plays in the natural history of AI. The mallard is distributed worldwide and, as previously mentioned, more AI viruses have been isolated from this species than any other wild avian species (Hinshaw et al, 1980;Stallknecht et al, 1990;Krauss et al, 2004;Munster et al, 2005;Olsen et al, 2006;Hesterberg et al, 2009). Mallards in the H5N2 and H3N8 treatment groups had an extended period of viral shedding, primarily via the cloaca.…”
Section: Discussionmentioning
confidence: 91%
“…This observation is consistent with historic surveillance results of higher isolation rates from mallards, and supports the important role that this species plays in the natural history of AI. The mallard is distributed worldwide and, as previously mentioned, more AI viruses have been isolated from this species than any other wild avian species (Hinshaw et al, 1980;Stallknecht et al, 1990;Krauss et al, 2004;Munster et al, 2005;Olsen et al, 2006;Hesterberg et al, 2009). Mallards in the H5N2 and H3N8 treatment groups had an extended period of viral shedding, primarily via the cloaca.…”
Section: Discussionmentioning
confidence: 91%
“…Experimental infections with H5N1 HPAIV (Brown et al, 2006(Brown et al, , 2008Keawcharoen et al, 2008) showed that most Anatids species are able to replicate and shed H5N1 HPAIV, half of the time without any clinical sign (Gaidet et al, 2010). Furthermore, almost all of healthy, free-living wild birds that have tested positive for H5N1 HPAI with no apparent clinical signs were Anatids (Chen et al, 2006;Saad et al, 2007;Hesterberg et al, 2009;OIE, 2009). The highest circulation rates of LPAIV in the field also have been detected for Anatids species (Olsen et al, 2006).…”
Section: Discussionmentioning
confidence: 94%
“…The prevalence of H5N1 in wild birds has been studied intensively in Europe since 2006, and the results of a 2006 survey have been reported recently (Hesterberg et al 2009). The survey showed that H5N1 viruses were found only rarely in dabbling ducks, but swans, diving ducks, mergansers and grebes showed higher rates of infection and usually associated with disease.…”
Section: Introductionmentioning
confidence: 99%